Marketing Strategy Of Museum Timah Indonesia As An Educational-Historical Tourism In Pangkalpinang, Bangka Belitung Island Province - Ricky Iddham Permana; I Made Sendra; I Putu Sudana (International Journal of Technology and Education Research, 2024)
This research aims to identify the existing conditions of tourism in the Museum Timah Indonesia and propose a marketing strategy for the Museum Timah Indonesia as an edu-historical tourism in Pangkalpinang City. This study uses a qualitative descriptive approach and is supported by quantitative data. Data collection through observation, interviews, documentation and questionnaires. Data analysis uses qualitative descriptive, IFAS, EFAS, IE matrix and SWOT matrix. The results of the study show that the existing condition of tourism at the Museum Timah Indonesia shows quite positive developments and continues to increase in recent years both from tourist visits, attractions, service facilities, promotional information and in terms of management organization. Meanwhile, in terms of internal factors (7P), the Indonesian Tin Museum has ten key indicators in the form of strengths and weaknesses and external factors (PESTEL) has nine indicators in the form of opportunities and threats. In the SWOT analysis, eight alternative strategies were obtained, consisting of strategies (S-O) taking advantage of the diversity of collections and technological advances and using service quality to support policies, (W-O) developing personal selling through technological advances and increasing public involvement with government policy support, (S-T) increasing advertising to overcome economic conditions and utilizing employee attitudes in facing social changes, and strategies (W-T) improve physical facilities to cope with economic conditions and cultural values and improve security procedures to cope with social changes and cultural values.